Co-implementation of precision nutrient management in long-term conservation agriculture-based systems: A step towards sustainable energy-water-food nexus - Parihar, Chiter Mal; Meena, Bolta Ram; Nayak, Harisankar; Patra, Kiranmoy; Sena, Dipaka Ranjan; Singh, Raj; Jat, Shankar Lal; Sharma, Dinesh Kumar; Mahala, Deep Mohan; Patra, Sridhar; Rupesh; Rathi, Neelmani; et al. (Elsevier, 2022)
The conventionally managed cereal-based cropping systems in the Indo-Gangetic Plains (IGP) of South Asia are energy intensive that overwhelm the farm profits and the environmental footprint. This research addresses a complex nexus between yield-energy-water-GHG footprints-economics of conservation agriculture (CA)-based intensified maize-wheat-mungbean rotation. This study evaluated the effect of long-term CA (2012–2020) with optimum nutrient management (2017–20) on energy budgeting, productivity, water and C-footprints, Water productivity (WP), and economics of the CA-based maize-wheat-mungbean system. CA-based permanent bed- and zero tillage flatbed with preceding crop residue retention were compared with the conventional till with preceding crop residue incorporation. These treatments were factored over three-nutrient management alternatives, i.e., GreenSeeker®-guided-N, site-specific nutrient management (SSNM), and recommended fertilizers' dose (Ad-hoc), were compared with farmers' fertilizers practices (FFP). Permanent bed and zero tillage treatments registered higher systems' productivity (18.2 and 12.0%), net returns (44.7 and 34.7%) and water productivity (35.6% and 22.1%), and C-sequestration (54.8 and 62.3%), respectively, over conventional till. Permanent bed- and zero tillage treatments increased the systems' net energy (NE), energy use efficiency (EUE), energy productivity (EP), and energy intensity (EI) by 22.6 and 14.0; 10.1 and 5.6; 9.7 and 5.4; 28.3 and 24.0%, respectively, over conventional till. Conventional till recorded higher net CO2-eq emission (26.5 and 27.2%), C-footprint (20.8 and 14.5%), and water footprint (27.3 and 18.0%) than permanent bed- and zero tillage treatments. SSNM increased the system's productivity, water productivity, and energy use efficiency, while reducing the system's water- and C-footprints and net CO2-eq emission. Thus, adopting permanent beds as a crop establishment method with SSNM could be a feasible alternative to attain higher productivity, profitability, and resource use efficiency in the maize-wheat-mungbean system in northwest India.